2021
DOI: 10.1097/htr.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Neurodegeneration Across Chronic Stages of Severe Traumatic Brain Injury

Abstract: Objective: To examine the trajectory of structural gray matter changes across 2 chronic periods of recovery in individuals who have sustained severe traumatic brain injury (TBI), adding to the growing literature indicating that neurodegenerative processes occur in the months to years postinjury. Participants: Patients who experienced posttraumatic amnesia of 1 hour or more, and/or scored 12 or less on the Glasgow Coma Scale at the emergency department or the scene of the accident, and/or had positive brain ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“… 19 , 46 After moderate–severe TBI, hippocampal volumetric decrements have been observed and may continue to progress for years after the injury event. 47 , 48 In the context of dementia, TBI may introduce vulnerabilities to hippocampal neurodegeneration, such as vascular dysfunction, 49 thereby increasing risk of these NPS by similar mechanisms as have been proposed outside the context of dementia (see Bray et al. 19 and Grace 46 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“… 19 , 46 After moderate–severe TBI, hippocampal volumetric decrements have been observed and may continue to progress for years after the injury event. 47 , 48 In the context of dementia, TBI may introduce vulnerabilities to hippocampal neurodegeneration, such as vascular dysfunction, 49 thereby increasing risk of these NPS by similar mechanisms as have been proposed outside the context of dementia (see Bray et al. 19 and Grace 46 ).…”
Section: Discussionmentioning
confidence: 93%
“…19,46 After moderate-severe TBI, hippocampal volumetric decrements have been observed and may continue to progress for years after the injury event. 47,48 In the context of dementia, TBI may introduce vulnerabilities to hippocampal neurodegeneration, such as vascular dysfunction, 49 thereby increasing risk of these NPS by similar mechanisms as have been proposed outside the context of dementia (see Bray et al 19 and Grace 46 ). The present study found that risk of this MBI domain was increased solely in the more severe group and that increased risk appeared to be more pronounced later in dementia progression; while these are in line with this possible explanation, evidence in support of this proposed mechanism is preliminary and further study is required.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study samples' data were obtained from a longitudinal, prospective study investigating TBI recovery (The Toronto TBI Recovery Study) (Adnan et al, 2013;Belchev et al, 2021;Greenberg, Mikulis, Ng, DeSouza, & Green, 2008;Miller, Colella, Mikulis, Maller, & Green, 2013;Ng et al, 2008;Terpstra, Girard, Colella, & Green, 2017;Till, Colella, Verwegen, & Green, 2008). A total of 105 participants with clinically confirmed TBI were recruited, and after quality control, 67 participants were included in the present study.…”
Section: Tbi Participantsmentioning
confidence: 99%
“…Previous studies, including ones that have examined the cohort assessed here, have described ongoing losses in brain volume, including subcortical structures, white matter, and the cortex over the months and years following moderate-severe TBI (Belchev et al, 2021;Bendlin et al, 2008;Brezova et al, 2014;Cole et al, 2018;Gooijers et al, 2016;O'Phelan, Otoshi, Ernst, & Chang, 2018;Sidaros et al, 2009). While these studies provide substantial evidence for volumetric changes in both grey and white matter following moderate-severe TBI, no longitudinal studies in adults have investigated changes to the two cortical surface-based morphometry measures that contribute to volume: cortical thickness (CT) and cortical surface area (CSA).…”
Section: Introductionmentioning
confidence: 99%